Influence of Bottom Ash Replacements as Fine Aggregate on the Property of Cellular Concrete with Various Foam Contents - Patchara Onprom; Krit Chaimoon; Raungrut Cheerarot (Advances in Materials Science and Engineering)
This research focuses on evaluating the feasibility of utilizing bottom ash from coal burning power plants as a fine aggregate in cellular concrete with various foam contents. Flows of all mixtures were controlled within 45 ± 5% and used foam content at 30%, 40%, 50%, 60%, and 70% by volume of mixture. Bottom ash from Mae Moh power plant in Thailand was used to replace river sand at the rates of 0%, 25%, 50%, 75%, and 100% by volume of sand. Compressive strength, water absorption, and density of cellular concretes were determined at the ages of 7, 14, and 28 days. Nonlinear regression technique was developed to construct the mathematical models for predicting the compressive strength, water absorption, and density of cellular concrete. The results revealed that the density of cellular concrete decreased while the water absorption increased with an increase in replacement level of bottom ash. From the experimental results, it can be concluded that bottom ash can be used as fine aggregate in the cellular concrete. In addition, the nonlinear regression models give very high degree of accuracy (R2>0.99).